The origins of ancient Vietnam - Kim, Nam C. (Oxford studies in the archaeology of ancient states, 2015)
'The Origins of Ancient Vietnam' explores the genesis of civilisation in the Red River Delta of Vietnam and how it can inform our understanding of ancient societies, generally, and the foundations of Vietnamese culture, specifically